2016
DOI: 10.1103/physrevd.93.085029
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop five-point all-plus helicity Yang-Mills amplitude

Abstract: We re-compute the recently derived two-loop five-point all plus Yang-Mills amplitude using Unitarity and Recursion. Recursion requires augmented recursion to determine the sub-leading pole. Using these methods the simplicity of this amplitude is understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 43 publications
10
107
0
Order By: Relevance
“…In D-dimensional unitarity the cuts are computed in D = 4 − 2ǫ dimensions where, typically, the components of the cuts are considerably more complicated than in four dimensions. In [4] it was demonstrated that fourdimensional unitarity techniques [5,6] blended with a knowledge of the singular structure of the amplitude could reproduce this form in a straightforward way. The four-dimensional approach was also used to calculate the six-point amplitude [7,8] which was subsequently verified [9].…”
Section: Introductionmentioning
confidence: 99%
“…In D-dimensional unitarity the cuts are computed in D = 4 − 2ǫ dimensions where, typically, the components of the cuts are considerably more complicated than in four dimensions. In [4] it was demonstrated that fourdimensional unitarity techniques [5,6] blended with a knowledge of the singular structure of the amplitude could reproduce this form in a straightforward way. The four-dimensional approach was also used to calculate the six-point amplitude [7,8] which was subsequently verified [9].…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of this approach have been applied to theories such as quantum chromodynamics at one loop [2][3][4] and more recently at two loops [5][6][7]. However, the most powerful applications to date have been to the planar limit of N = 4 super-YangMills (SYM) theory in four dimensions [8,9].…”
Section: Jhep02(2017)137mentioning
confidence: 99%
“…Therefore the singular behavior of the sixpoint amplitude is controlled by a single coefficient function, which we denote by U 6 and JHEP02(2017)137 whose limiting behavior takes an especially simple form. 6 Up to power-suppressed terms, the limit of U 6 was found to be a polynomial in log(uw/v), whose coefficients are rational linear combinations of zeta values, and whose overall weight is 2L. Here, u, v, and w are the three dual conformal invariant cross ratios for the hexagon, whose expressions in terms of six-point kinematics are…”
Section: Jhep02(2017)137mentioning
confidence: 99%
See 2 more Smart Citations